(untitled) (Indian Journal of Animal Production and Management, 2015)
The study was conducted at Pig Breeding Farm, Ranchi Veterinary College, Kanke, Ranchi. It deals with evaluating unconventional silkworm pupae (SWP) as an economic substitute of protein concentrate. Eighteen (18) growing crossbred piglets (3-3.5 months) were randomly divided into 3 groups (T1, T2, and T3). Piglets of group T1 (control) were fed standard concentrate mixture. In group T2 and T3, the fish meal of ration T1 was replaced with silk worm pupae @ 50 and 100 percent on protein equivalent basis, respectively. Significantly highest feed consumption was observed in group I followed by group II and III. At the end of experiment (7th fortnight) the feed conversion ratio was observed to be lowest in T2 (2.15 ± 0.16) followed by T1 (2.63 ± 0.34) and T3 (2.68 ± 0.22). Non-significant but highest body weight gain were observed for group I (77.75 ± 4.34) followed by groups II (72.75 ± 4.57) and III (66.08± 5.76). The average cost per kg body weight gain (Rs.) was observed to be 54.02, 50.72 and 45.72, respectively for group I, II and III. Hence, silkworm pupae meal may be a used in place of fish meal to make the ration cost effective, without affecting the performance adversely.